base-4.11.1.0: Basic libraries

Data.Bifoldable

Description

Since: base-4.10.0.0

Synopsis

# Documentation

class Bifoldable p where Source #

Bifoldable identifies foldable structures with two different varieties of elements (as opposed to Foldable, which has one variety of element). Common examples are Either and '(,)':

instance Bifoldable Either where
bifoldMap f _ (Left  a) = f a
bifoldMap _ g (Right b) = g b

instance Bifoldable (,) where
bifoldr f g z (a, b) = f a (g b z)

A minimal Bifoldable definition consists of either bifoldMap or bifoldr. When defining more than this minimal set, one should ensure that the following identities hold:

bifold ≡ bifoldMap id id
bifoldMap f g ≡ bifoldr (mappend . f) (mappend . g) mempty
bifoldr f g z t ≡ appEndo (bifoldMap (Endo . f) (Endo . g) t) z


If the type is also a Bifunctor instance, it should satisfy:

'bifoldMap' f g ≡ 'bifold' . 'bimap' f g

which implies that

'bifoldMap' f g . 'bimap' h i ≡ 'bifoldMap' (f . h) (g . i)

Since: base-4.10.0.0

Minimal complete definition

Methods

bifold :: Monoid m => p m m -> m Source #

Combines the elements of a structure using a monoid.

bifold ≡ bifoldMap id id

Since: base-4.10.0.0

bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> p a b -> m Source #

Combines the elements of a structure, given ways of mapping them to a common monoid.

bifoldMap f g
≡ bifoldr (mappend . f) (mappend . g) mempty

Since: base-4.10.0.0

bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> p a b -> c Source #

Combines the elements of a structure in a right associative manner. Given a hypothetical function toEitherList :: p a b -> [Either a b] yielding a list of all elements of a structure in order, the following would hold:

bifoldr f g z ≡ foldr (either f g) z . toEitherList

Since: base-4.10.0.0

bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> p a b -> c Source #

Combines the elements of a structure in a left associative manner. Given a hypothetical function toEitherList :: p a b -> [Either a b] yielding a list of all elements of a structure in order, the following would hold:

bifoldl f g z
≡ foldl (acc -> either (f acc) (g acc)) z . toEitherList

Note that if you want an efficient left-fold, you probably want to use bifoldl' instead of bifoldl. The reason is that the latter does not force the "inner" results, resulting in a thunk chain which then must be evaluated from the outside-in.

Since: base-4.10.0.0

Instances
 # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => Either m m -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> Either a b -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> Either a b -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> Either a b -> c Source # # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (a, b) -> c Source # # Since: base-4.10.0.0 Instance detailsDefined in Data.Semigroup Methodsbifold :: Monoid m => Arg m m -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> Arg a b -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> Arg a b -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> Arg a b -> c Source # # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (x, m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (x, a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (x, a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (x, a, b) -> c Source # Bifoldable (Const :: * -> * -> *) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => Const m m -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> Const a b -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> Const a b -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> Const a b -> c Source # Bifoldable (K1 i :: * -> * -> *) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => K1 i m m -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> K1 i a b -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> K1 i a b -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> K1 i a b -> c Source # Bifoldable ((,,,) x y) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (x, y, m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (x, y, a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (x, y, a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (x, y, a, b) -> c Source # Bifoldable ((,,,,) x y z) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (x, y, z, m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (x, y, z, a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (x, y, z, a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (x, y, z, a, b) -> c Source # Bifoldable ((,,,,,) x y z w) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (x, y, z, w, m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (x, y, z, w, a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (x, y, z, w, a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (x, y, z, w, a, b) -> c Source # Bifoldable ((,,,,,,) x y z w v) # Since: base-4.10.0.0 Instance detailsDefined in Data.Bifoldable Methodsbifold :: Monoid m => (x, y, z, w, v, m, m) -> m Source #bifoldMap :: Monoid m => (a -> m) -> (b -> m) -> (x, y, z, w, v, a, b) -> m Source #bifoldr :: (a -> c -> c) -> (b -> c -> c) -> c -> (x, y, z, w, v, a, b) -> c Source #bifoldl :: (c -> a -> c) -> (c -> b -> c) -> c -> (x, y, z, w, v, a, b) -> c Source #

bifoldr' :: Bifoldable t => (a -> c -> c) -> (b -> c -> c) -> c -> t a b -> c Source #

As bifoldr, but strict in the result of the reduction functions at each step.

Since: base-4.10.0.0

bifoldr1 :: Bifoldable t => (a -> a -> a) -> t a a -> a Source #

A variant of bifoldr that has no base case, and thus may only be applied to non-empty structures.

Since: base-4.10.0.0

bifoldrM :: (Bifoldable t, Monad m) => (a -> c -> m c) -> (b -> c -> m c) -> c -> t a b -> m c Source #

Right associative monadic bifold over a structure.

Since: base-4.10.0.0

bifoldl' :: Bifoldable t => (a -> b -> a) -> (a -> c -> a) -> a -> t b c -> a Source #

As bifoldl, but strict in the result of the reduction functions at each step.

This ensures that each step of the bifold is forced to weak head normal form before being applied, avoiding the collection of thunks that would otherwise occur. This is often what you want to strictly reduce a finite structure to a single, monolithic result (e.g., bilength).

Since: base-4.10.0.0

bifoldl1 :: Bifoldable t => (a -> a -> a) -> t a a -> a Source #

A variant of bifoldl that has no base case, and thus may only be applied to non-empty structures.

Since: base-4.10.0.0

bifoldlM :: (Bifoldable t, Monad m) => (a -> b -> m a) -> (a -> c -> m a) -> a -> t b c -> m a Source #

Left associative monadic bifold over a structure.

Since: base-4.10.0.0

bitraverse_ :: (Bifoldable t, Applicative f) => (a -> f c) -> (b -> f d) -> t a b -> f () Source #

Map each element of a structure using one of two actions, evaluate these actions from left to right, and ignore the results. For a version that doesn't ignore the results, see bitraverse.

Since: base-4.10.0.0

bifor_ :: (Bifoldable t, Applicative f) => t a b -> (a -> f c) -> (b -> f d) -> f () Source #

As bitraverse_, but with the structure as the primary argument. For a version that doesn't ignore the results, see bifor.

>>> > bifor_ ('a', "bc") print (print . reverse)
'a'
"cb"


Since: base-4.10.0.0

bimapM_ :: (Bifoldable t, Applicative f) => (a -> f c) -> (b -> f d) -> t a b -> f () Source #

Alias for bitraverse_.

Since: base-4.10.0.0

biforM_ :: (Bifoldable t, Applicative f) => t a b -> (a -> f c) -> (b -> f d) -> f () Source #

Alias for bifor_.

Since: base-4.10.0.0

bimsum :: (Bifoldable t, Alternative f) => t (f a) (f a) -> f a Source #

Alias for biasum.

Since: base-4.10.0.0

bisequenceA_ :: (Bifoldable t, Applicative f) => t (f a) (f b) -> f () Source #

Alias for bisequence_.

Since: base-4.10.0.0

bisequence_ :: (Bifoldable t, Applicative f) => t (f a) (f b) -> f () Source #

Evaluate each action in the structure from left to right, and ignore the results. For a version that doesn't ignore the results, see bisequence.

Since: base-4.10.0.0

biasum :: (Bifoldable t, Alternative f) => t (f a) (f a) -> f a Source #

The sum of a collection of actions, generalizing biconcat.

Since: base-4.10.0.0

biList :: Bifoldable t => t a a -> [a] Source #

Collects the list of elements of a structure, from left to right.

Since: base-4.10.0.0

binull :: Bifoldable t => t a b -> Bool Source #

Test whether the structure is empty.

Since: base-4.10.0.0

bilength :: Bifoldable t => t a b -> Int Source #

Returns the size/length of a finite structure as an Int.

Since: base-4.10.0.0

bielem :: (Bifoldable t, Eq a) => a -> t a a -> Bool Source #

Does the element occur in the structure?

Since: base-4.10.0.0

bimaximum :: forall t a. (Bifoldable t, Ord a) => t a a -> a Source #

The largest element of a non-empty structure.

Since: base-4.10.0.0

biminimum :: forall t a. (Bifoldable t, Ord a) => t a a -> a Source #

The least element of a non-empty structure.

Since: base-4.10.0.0

bisum :: (Bifoldable t, Num a) => t a a -> a Source #

The bisum function computes the sum of the numbers of a structure.

Since: base-4.10.0.0

biproduct :: (Bifoldable t, Num a) => t a a -> a Source #

The biproduct function computes the product of the numbers of a structure.

Since: base-4.10.0.0

biconcat :: Bifoldable t => t [a] [a] -> [a] Source #

Reduces a structure of lists to the concatenation of those lists.

Since: base-4.10.0.0

biconcatMap :: Bifoldable t => (a -> [c]) -> (b -> [c]) -> t a b -> [c] Source #

Given a means of mapping the elements of a structure to lists, computes the concatenation of all such lists in order.

Since: base-4.10.0.0

biand :: Bifoldable t => t Bool Bool -> Bool Source #

biand returns the conjunction of a container of Bools. For the result to be True, the container must be finite; False, however, results from a False value finitely far from the left end.

Since: base-4.10.0.0

bior :: Bifoldable t => t Bool Bool -> Bool Source #

bior returns the disjunction of a container of Bools. For the result to be False, the container must be finite; True, however, results from a True value finitely far from the left end.

Since: base-4.10.0.0

biany :: Bifoldable t => (a -> Bool) -> (b -> Bool) -> t a b -> Bool Source #

Determines whether any element of the structure satisfies its appropriate predicate argument.

Since: base-4.10.0.0

biall :: Bifoldable t => (a -> Bool) -> (b -> Bool) -> t a b -> Bool Source #

Determines whether all elements of the structure satisfy their appropriate predicate argument.

Since: base-4.10.0.0

bimaximumBy :: Bifoldable t => (a -> a -> Ordering) -> t a a -> a Source #

The largest element of a non-empty structure with respect to the given comparison function.

Since: base-4.10.0.0

biminimumBy :: Bifoldable t => (a -> a -> Ordering) -> t a a -> a Source #

The least element of a non-empty structure with respect to the given comparison function.

Since: base-4.10.0.0

binotElem :: (Bifoldable t, Eq a) => a -> t a a -> Bool Source #

binotElem is the negation of bielem.

Since: base-4.10.0.0

bifind :: Bifoldable t => (a -> Bool) -> t a a -> Maybe a Source #

The bifind function takes a predicate and a structure and returns the leftmost element of the structure matching the predicate, or Nothing if there is no such element.

Since: base-4.10.0.0